The Influence of Face on Online Purchases: Evidence From China - Sun, Gong; Shen, Famei; Ma, Xinyi (Frontiers in Psychology, 2021)
This study examines the influence of an indigenous concept – face on online purchases in China. Specifically, we test the mediating role of materialism and the moderating role of price consciousness. We conduct a survey of 315 Chinese consumers. The results demonstrate that consumers tend to make online purchases to satisfy some facets of their materialistic needs and then gain face, especially for those highly conscious of price. The current research can help both scholars and practitioners better understand Chinese consumers and their decision-making processes. Implications, limitations, and directions for future research are also provided.